Hemoperitoneum secondary to necrotizing hemorrhagic cholecystitis (Revista Argentina de Cirugía, 2021)
Anticoagulated 70 year-old man presents acute cholecystitis with hemodynamic descompensation. Emergency laparoscopy is done; and hemoperitoneum is found due to necrotizing hemorrhagic cholecystitis. The vesicular pedicle is difficult to identify; therefore, laparoscopy is converted into open surgery. The cystic duct is identified through intraoperative cholangiography. The histopathological study reveals acute necrohemorrhagic cholecystitis developed on a chronic cholecystitis with no malignant transformation. Bleeding is an uncommon complication of acute cholecystitis frequently associated with coagulopathies. Clinical presentation varies so a high index of suspicion and early diagnosis is required for emergency surgical management.
Keywords: acute cholecystitis; hemoperitoneum; hemorrhagic cholecystitis